A Eu3+-based high sensitivity ratiometric fluorescence sensor for determination of tetracycline combining bi-functional carbon dots by surface functionalization and heteroatom doping. (May 2022) - Yao, Ruihong; Li, Zhijian; Huo, Panpan; Gong, Congcong; Li, Jin; Fan, Congbin; Pu, Shouzhi
Abstract: A ratiometric fluorescence sensor based on Cu-CDs–COOH–Eu was proposed and used to highly sensitive detection of Tetracycline (TC) residues in complex samples. Combination with surface functionalization of carboxyl group and heteroatom doping of Cu 2+, the bi-functional carbon dots (Cu-CDs-COOH) were prepared, which exhibited an outstanding fluorescence properties and optical stability. Thanks to the Cu-CDs-COOH rich in carboxyl groups, Eu 3+ can effectively chelate with Cu-CDs-COOH which still maintained excellent optical properties (denoted as Cu-CDs–COOH–Eu). When TC was presented in the sensing system of Cu-CDs–COOH–Eu, the strong blue emission of Cu–COOH was quenched at 467 nm based on inner filter effect while the characteristic peak of Eu 3+ at 625 nm was enhanced via antenna effect. Herein, a ratiometric fluorescence sensor was built, which was able to detect TC in the range of 0.4–60 μM with a low limit detection of 36.1 nM. The proposed method also showed a satisfactory result of determination TC reliably and accurately in complex samples. Graphical abstract: Using an environmentally friendly method, the bi-functional carbon dots were easily synthesized by surface functionalization of carboxyl group and heteroatom doping of Cu 2+, which have outstanding optical properties and stability. Thanks to the Cu-CDs-COOH rich in carboxyl groups, Eu 3+ can effectively chelate with Cu-CDs-COOH. A Cu-CDs–COOH–Eu ratiometric fluorescence sensor was successfully proposed and applied for detection of tetracycline (TC). In the present of TC, the strong blue fluorescence emission of Cu-CDs–COOH–Eu at 467 nm was quenched due to inner filter effect (IFE), while Eu 3+ was sensitized by the TC (antenna effect, AE) that red fluorescence emission of Eu 3+ at 626 nm can be observed. Image 1 Highlights: The Cu-CDs-COOH is easily prepared by surface functionalization carboxyl group and heteroatom doping of Cu 2+ . A ratiometric fluorescent sensor is proposed by coordination Eu 3+ with carboxyl group on Cu-CDs-COOH. The proposed sensor realizes a rapid, highly sensitive and selective for detection of TC. The proposed sensor shows a satisfactory result on detection of TC in complex real samples.